An investigation into factors contributing to non-adherence of patients collecting medicine from central chronic medication dispensing and distribution pick-up points in the Tshwane disctrict - Rossouw, Seugnette (University of Pretoria, 2023)
Dissertation (MNur (Nursing Science))--University of Pretoria, 2022.